Non high density lipoprotein to high density lipoprotein cholesterol ratio and type 2 diabetes in Middle aged and Elderly Chinese - Jiacong Tan; Huaxin Zhu; Yanyang Zeng; Jiawei Li; Yeyu Zhao; Xue Xiao; Meihua Li (Scientific Reports, 2025)
Abstract The aim of this study was to assess the potential association between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) and type 2 diabetes mellitus (T2DM) in a middle-aged and elderly Chinese population using data from the China Health and Retirement Longitudinal Study (CHARLS) from 2011 to 2015. Methods We used data from CHARLS 2011 as baseline data and follow-up data from 2015. NHHR was used as a continuous and categorical variable, and multivariate logistic regression modeling was used to explore its relationship with T2DM. Three models were developed to adjust for the possible effects of 14 factors on the outcomes. Restricted cubic spline was used to check for possible nonlinear associations, and subgroup and interaction analyses were used to assess differences between groups. Results A total of 7847 subjects were enrolled in the study, of whom 948 (12.1%) were diagnosed with T2DM. The last NHHR quartile group (Q4) presented the highest risk of T2DM (OR, 1.115, 95% CI, 1.088–1.141) after accounting for all covariates. Restricted cubic spline regression modeling revealed a nonlinear relationship between NHHR and T2DM (p for nonlinear = 0.001). The results of the subgroup analyses were consistent across the categories, indicating a significant positive correlation. Interaction analyses revealed significant interactions between NHHR and age, gender and marital status. Conclusion In the middle-aged and elderly population in China, there is a strong correlation between elevated NHHR and increased risk of T2DM onset. The relationship between NHHR and T2DM can be further investigated in the future to provide reference for the development of more accurate prediction models.